THERMODYNAMIC DATA FOR FE-BEARING PHASES OBTAINED USING NOBLE METAL ALLOYS AS REDOX SENSORS - Woodland A.B.; O'Neill H.S.C. (My University, 1997)
The technique of using noble metal alloys as redox sensors has been adapted for use in hydrothermal experiments in the piston-cylinder apparatus at the reduced conditions of the iron-wustite (IW) buffer. The required high fH2 was maintained for several days using thick-walled (0.5 mm) Ag outer capsules. Such conditions permit the Gibbs free energy of Fe2+-bearing phases to be obtained from the composition of the co-existing alloy. The Ir-Fe system is more amenable than either Pt-Fe or Pd-Fe since only one phase (γ-fcc) is stable in this system over a large temperature range, and the solubility of Ag (capsule material) in Ir is negligible.Experiments with the assemblage fayalite-quartz-Fe (in alloy) (QFI) were used as a test of the method by comparison with the electrochemical measurements of O'Neill (1987a). The resulting agreement demonstrates the utility of the method between 700 and 1000°C at ~ 10 kbar. Further experiments with FeSiO3-bearing assemblages (ferrosilite-quartz-iron, PYQI, and ferrosilite-fayalite-iron, PYFAI) indicate the method is viable up to 20 kbar and between 700°C and 1000°C. However, small systematic deviations of about 1-2 kJ per mole of O2 in the quartz-saturated experiments are interpreted to indicate that the high solubility of SiO2 at high pressures may result in a lowering of the H2O activity in the co-existing supercritical fluid phase.